Local Remelting in Laser Powder Bed Fusion - Janno Lehmann; Martin Weise; Markus Köhler; Frank von Lacroix; Vasily Ploshikhin; Klaus Dilger (Journal of Manufacturing and Materials Processing)
In Laser Powder Bed Fusion, process material defects such as a lack of fusion, powder inclusions and cavities occur repeatedly by chance. These stochastically distributed defects can significantly reduce the mechanical performance of the components during operation. Possible in situ repair solutions such as multiple remelting of specific layer areas are promising approaches to avoid these defects in the finished component, thus improving the overall properties. In this context, the present study investigates the remelting of artificially introduced defects using the example of M789 tool steel. In the first step, the process parameter settings and mechanical properties were evaluated using a tensile test, and the density of the local repair was examined using X-ray computer tomography and a metallographic analysis. The results demonstrate that the mechanical properties of the tensile test are comparable with those of the reference samples while successfully increasing the component quality. This indicates that defects that arise during the process can be remelted without the loss of mechanical characteristics.